2017
DOI: 10.1111/jan.13474
|View full text |Cite
|
Sign up to set email alerts
|

Effects and associations of nutrition in patients with venous leg ulcers: A systematic review

Abstract: Current evidence suggests that venous leg ulcer patients are more likely to be overweight or obese. However, evidence for weight management improving wound healing is lacking. Micronutrients, including vitamin D and folic acid, may improve wound healing in at-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 68 publications
(280 reference statements)
3
47
0
6
Order By: Relevance
“…Three SRs related to weight management were published, including one on nutritional status and supplements and two on exercising . The authors reported that increased body mass index was associated with delayed wound healing, but the evidence of effectiveness of weight management in improving VLU healing is lacking . However, micronutrients, including vitamin D and folic acid, may improve wound healing in at‐risk patients .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three SRs related to weight management were published, including one on nutritional status and supplements and two on exercising . The authors reported that increased body mass index was associated with delayed wound healing, but the evidence of effectiveness of weight management in improving VLU healing is lacking . However, micronutrients, including vitamin D and folic acid, may improve wound healing in at‐risk patients .…”
Section: Resultsmentioning
confidence: 99%
“…The authors reported that increased body mass index was associated with delayed wound healing, but the evidence of effectiveness of weight management in improving VLU healing is lacking . However, micronutrients, including vitamin D and folic acid, may improve wound healing in at‐risk patients . An SR assessing the effectiveness of the oral nutritional supplements in VLU management is in progress .…”
Section: Resultsmentioning
confidence: 99%
“…Excess weight and obesity are established independent risk factors for venous ulceration and are associated with delayed VLU healing, yet only 76 studies (just over half of our sample) reported on the BMI of their included patients. The prevalence of obesity (BMI >30) among people with VLU is gaining more attention with one study ( N = 1,163 patients) reporting that 33% had a BMI >30 and a further study reporting 60% of people with VLU being either overweight or obese .…”
Section: Discussionmentioning
confidence: 99%
“…Encourage activities that promote good skin care and hygiene, reduction of leg oedema, good nutrition, obesity reduction, and improvement in general health and wellbeing 28293031. Exercise is safe, and it reverses the effects of venous hypertension but does not promote ulcer healing per se 282932…”
Section: How To Treat Venous Leg Ulcers?mentioning
confidence: 99%